Osmolyte regulation by TonEBP/NFAT5 during anoxia-recovery and dehydration–rehydration stresses in the freeze-tolerant wood frog (Rana sylvatica) - Al-attar,Rasha; Zhang,Yichi; Storey,Kenneth B. (PeerJ, 2017)
Background The wood frog, Rana sylvatica, tolerates freezing as a means of winter survival. Freezing is considered to be an ischemic/anoxic event in which oxygen delivery is significantly impaired. In addition, cellular dehydration occurs during freezing because water is lost to extracellular compartments in order to promote freezing. In order to prevent severe cell shrinkage and cell death, it is important for the wood frog to have adaptive mechanisms for osmoregulation. One important mechanism of cellular osmoregulation occurs through the cellular uptake/production of organic osmolytes like sorbitol, betaine, and myo-inositol. Betaine and myo-inositol are transported by the proteins BGT-1 and SMIT, respectively. Sorbitol on the other hand, is synthesized inside the cell by the enzyme aldose reductase. These three proteins are regulated at the transcriptional level by the transcription factor, NFAT5/TonEBP. Therefore, the objective of this study was to elucidate the role of NFAT5/TonEBP in regulating BGT-1, SMIT, and aldose reductase, during dehydration and anoxia in the wood frog muscle, liver, and kidney tissues. Methods Wood frogs were subjected to 24 h anoxia-4 h recovery and 40% dehydration-full rehydration experiments. Protein levels of NFAT5, BGT-1, SMIT, and aldose reductase were studied using immunoblotting in muscle, liver, and kidney tissues. Results Immunoblotting results demonstrated downregulations in NFAT5 protein levels in both liver and kidney tissues during anoxia (decreases by 41% and 44% relative to control for liver and kidney, respectively). Aldose reductase protein levels also decreased in both muscle and kidney tissues during anoxia (by 37% and 30% for muscle and kidney, respectively). On the other hand, BGT-1 levels increased during anoxia in muscle (0.9-fold compared to control) and kidney (1.1-fold). Under 40% dehydration, NFAT5 levels decreased in liver by 53%. Aldose reductase levels also decreased by 42% in dehydrated muscle, and by 35% in dehydrated liver. In contrast, BGT-1 levels increased by 1.4-fold in dehydrated liver. SMIT levels also increased in both dehydrated muscle and liver (both by 0.8-fold). Discussion Overall, we observed that osmoregulation through an NFAT5-mediated pathway is both tissue- and stress-specific. In both anoxia and dehydration, there appears to be a general reduction in NFAT5 levels resulting in decreased aldose reductase levels, however BGT-1 and SMIT levels still increase in certain tissues. Therefore, the regulation of osmoregulatory genes during dehydration and anoxia occurs beyond the transcriptional level, and it possibly involves RNA processing as well. These novel findings on the osmoregulatory mechanisms utilized by the wood frog advances our knowledge of osmoregulation during anoxia and dehydration. In addition, these findings highlight the importance of using this model to study molecular adaptations during stress.
Keywords: Nuclear factor of activated T cells; Rana sylvatica; Dehydration; Anoxia; Immunoblotting; Osmotic stress